The primary way : philosophy of Yijing - Cheng, Zhongying, 1935- (SUNY Press, 2020)
In The Primary Way, the distinguished scholar of Chinese philosophy Chung-ying Cheng synthesizes his lifetime of work on the Yijing, also known as the I Ching or Book of Changes--Back cover.
Keywords: Yi jing.; Yi jing; Philosophy, Chinese.; Philosophie chinoise.; Philosophy, Chinese; PHILOSOPHY / Metaphysics